Prenatal exposure to excess testosterone modifies the developmental trajectory of the insulin-like growth factor system in female sheep - Crespi, Erica J (Blackwell Science Inc, 2006)
Experimental elevation of maternal testosterone (T) from 30 to 90 days of gestation leads to intrauterine growth retardation (IUGR) and increased prepubertal growth rate in female lambs. This study tested the hypothesis that prenatal T treatment during mid-gestation alters the trajectory of the fetal insulin-like growth factor (IGF)–insulin-like growth factor binding protein (IGFBP) system to promote IUGR and subsequent postnatal catch-up growth in female lambs. Plasma IGF-I and IGFBPs were measured by radioimmunoassay and Western ligand blot, respectively, on 65, 90 and 140 days (d) of gestation, at birth, ∼5 months (prepubertal, the catch-up growth period), and ∼9.5 months (postpubertal). Northern blot analysis was used to measure hepatic mRNA content of IGF system components during fetal stages. At fetal 65 d, plasma protein and hepatic mRNA content of IGFBP-1, an inhibitor of IGF bioactivity, was elevated in prenatal T-treated fetuses although body weight did not differ. There was a transient increase in plasma IGF-I and IGFBP-3 concentrations at fetal 90 d in prenatal T-treated fetuses. Hepatic IGF-I mRNA and plasma IGFBP-3 content were reduced by 140 d when body weight was reduced in prenatal T-treated fetuses. Plasma IGFBP-2 content was significantly reduced in prenatal T-treated newborns, but by 4 months these females had significantly higher circulating IGF-I and IGFBP-3 concentrations and faster growth rates than control females. After puberty, plasma IGF-I remained elevated in prenatal T-treated females. These findings provide evidence that prenatal T excess programmes the developmental trajectory of the IGF/IGFBP system in female sheep to reduce IGF bioavailability during IUGR and increase IGF bioavailability during prepubertal catch-up growth.